BRET and Time-resolved FRET strategy to study GPCR oligomerization: from cell lines toward native tissues - Cottet, Martin; Faklaris, Orestis; Maurel, Damien; Scholler, Pauline; Doumazane, Etienne; Trinquet, Eric; Pin, Jean-Philippe R.; DURROUX, Thierry (Frontiers in Endocrinology, 2012)
The concept of oligomerization of G protein-coupled receptor (GPCR) opens new perspectives regarding physiological function regulation. The capacity of one GPCR to modify its binding and coupling properties by interacting with a second one can be at the origin of regulations unsuspected two decades ago. Although the concept is interesting, its validation at a physiological level is challenging and probably explains why receptor oligomerization is still a matter of debate. Demonstrating the direct interactions between two proteins is not trivial since few techniques present a spatial resolution allowing to conclude to close interactions. Resonance energy transfer (RET) strategies are actually the most convenient ones. During the last two decades, two of them, the Bioluminescent Resonance Energy Transfer (BRET) and Time-resolved Fluorescence Energy Transfer (TR-FRET) have been widely used since they exhibit high signal-to-noise ratio. Most of the experiments based on GPCR labeling have been performed in cell lines and it has been shown that all GPCRs have the propensity to form homo- or hetero-oligomers. However, whether these data can be extrapolated to GPCRs expressed in native tissues and explain receptor functioning in real life, remains an open question. Native tissues impose different constraints since GPCR sequences cannot be modified. Recently a fluorescent ligand-based GPCR labeling strategy combined to TR-FRET approach has been successfully used to prove the existence of GPCR oligomerization in native tissues. Although the RET based strategies are generally quite simple to implement, precautions have to be taken before concluding to the absence or the existence of specific interactions between receptors. For example, one should exclude the possibility of collision of receptors diffusing throughout the membrane leading to a specific FRET signal. We will review the advantages and the limits of different approaches and discuss the consequent perspectives.